The Comparison of Shunt Active Power Filter Structure for the Harmonic Elimination in AC-Electric Railway Systems - ตรงใจ ฐานันดร์ (Srinakharinwirot University Engineering Journal, 2018)
This paper presents the performance comparison of harmonic elimination in electric railway systems with two shunt active power filter (SAPF) structures: split capacitor structure and joint capacitor structure. The indicators of the comparison for the two SAPF structures are the total current harmonic distortion (%THDI), the ripple of DC bus voltage (% VDC(ripple)) and the dynamic response of DC bus voltage during load changes. The harmonic detection, synchronous reference frame (SRF method) is used for calculating the reference current of both SAPF structures. The conventional PI controllers are used to control the compensating current and regulate the DC bus voltage of SAPF. The hardware in the loop (HIL) simulation technique which process by Simulink/MATLAB program and TMS320C2000TM Experimenter Kit board is applied to simulate harmonic elimination in AC-electric railway systems. The simulation results show that both SAPF structures can provide good performance for harmonic elimination and the %THDI of source current after compensation are satisfied under the IEEE std 519-2014. Furthermore, the SAPF with joint capacitor structure gives less ripple of DC bus voltage than the split capacitor structure. However, the split capacitor structure has better dynamic response than the joint capacitor structure when loads in the system have been changed and greatly increased.